Dimensionally and oxidatively stable anion exchange membranes based on bication cross-linked poly(meta-terphenylene alkylene)s. (22nd February 2021) - Jiang, Tao; Zhou, Yiyang; Yang, Yake; Wu, Cheng; Fang, Huagao; Yang, Shanzhong; Wei, Haibing; Ding, Yunsheng
Abstract: Anion exchange membrane (AEM) is a key component for energy-conversion devices that enabling the use of non-noble electrocatalysts. After more than a decade of pursuit in alkaline-stable and high anion-conducting ionomers, aryl ether-free polyaromatics offer a promising candidate as an advanced AEM for use in fuel cell and electrolyzers. However, the traditional trade-off dilemma between conductivity and stability (e.g., chemical, dimensional, and mechanical stabilities etc.) of the membrane still remains. Here, we introduced a flexible bication cross-linker to doubly quaternary ammonium-tethered poly( meta -terphenylene alkylene) ionomers with high ion contents, aiming to improve the chemical and dimensional stabilities without compensate the ion-conducting merits. The designed flexible bication cross-linker is responsible for the microphase-separated morphology preservation in the cross-linked membranes. Although the water absorption decreased significantly as cross-linking content increasing, the ion conductivity of the cross-linked AEM was well retained, especially at elevated temperatures. Moreover, after cross-linking, a notable increase in chemical stability was observed, and the m -XPTPA40-2N with highest cross-linking density exhibited the best alkaline and oxidative stabilities. Owing to the mechanical robustness and high conductivity, a fuel cell fabricated with cross-linked membrane m -XPTPA40-2N showed a maximum power density of 302 mW cm −2 at a current density of 614 mA cm −2 . Overall, the results of this study provide a simple but efficient strategy to improve the performance of AEM. Graphical abstract: Image 1 Highlights: A flexible bication cross-link was introduced to mitigate the dilemma between ion conductivity and dimensional integrity. The morphology of AEM was well preserved after cross-linking. Bication cross-linked AEMs showed excellent chemical durability. A H2 –O2 fuel cell based on m -XPTPA40-2N AEM showed a peak power density of 302 mW cm −2 .